Estrés por pandemia covid 19 y su influencia en el comportamiento de un estudiante de octavo de básica de la Unidad Educativa San Carlos - Huacon Lascano, Yomira Elizabeth (2021)
This case study dealt with the subject of stress due to the Covid 19 pandemic and its influence on the behavior of an eighth grade student of the San Carlos Educational Unit, where the necessary data was collected for the elaboration of the case study through interviews and psychometric instruments such as clinical history, psychological interviews, psychological tests, which were applied to the patient. The results obtained were stress in the academic environment and moderate trait anxiety, mild state anxiety The diagnosis obtained was: according to DSM- 5 (308.3(F43.0) and (300.02(F41.1) Acute Stress Disorder and Generalized Anxiety Disorder. Some cognitive-behavioral techniques were carried out with the purpose of eliminating, decreasing or modifying certain behaviors presented by the patient, thus carrying out the appropriate psychotherapeutic intervention for the patient.